2019
DOI: 10.2478/hukin-2019-0016
|View full text |Cite
|
Sign up to set email alerts
|

Post‐Activation Potentiation: Is there an Optimal Training Volume and Intensity to Induce Improvements in Vertical Jump Ability in Highly‐Trained Subjects?

Abstract: The aim of this study was to compare the acute effects of performing half squats (HSs) with different loading intensities (1, 3, and 5 repetitions maximum [RM], and 60% 1RM) and a different number of sets (1, 2, and 3) on the countermovement jump (CMJ) performance of 18 highly‐trained male subjects. Participants were submitted to four experimental conditions (1RM, 3RM, 5RM, and 60% 1RM) in randomized order. The CMJ was assessed before and after each set. Differences in CMJ performance between the distinct expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 42 publications
(26 reference statements)
0
25
0
Order By: Relevance
“…< 5 minutes) potentiation responses have also been observed in some studies with both resistance [16,17] and ballistic [13] exercises. More importantly, several studies have suggested the necessity of individualized approaches as the generalization of findings is often not valid for individual responses in the same studies [6,[16][17][18]. In this regard, if we consider our recent taxonomy proposal [7], which highlights the necessity of better identifying the main factors of PAPE as CA, the verification test, and population, it may be suggested that other potential moderators (e.g.…”
Section: Pape Factors and Their Moderatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…< 5 minutes) potentiation responses have also been observed in some studies with both resistance [16,17] and ballistic [13] exercises. More importantly, several studies have suggested the necessity of individualized approaches as the generalization of findings is often not valid for individual responses in the same studies [6,[16][17][18]. In this regard, if we consider our recent taxonomy proposal [7], which highlights the necessity of better identifying the main factors of PAPE as CA, the verification test, and population, it may be suggested that other potential moderators (e.g.…”
Section: Pape Factors and Their Moderatorsmentioning
confidence: 99%
“…Further, the physiological profile associated to the demands of each sport (individual vs. team sports; endurance vs. power sports) can importantly influence both PAPE factors and responses [7,19]. But this moderator is not always considered, specifically in studies that mix athletes from different sports [18,35].…”
Section: Pape Factors and Their Moderatorsmentioning
confidence: 99%
“…The athlete must resist the inertial force of the flywheel by developing a maximal voluntary braking action (i.e., eccentric leg contraction), which is characterized by a higher solicitation of type II fibers and a greater cortical activity ( MarotoIzquierdo et al, 2017 ; Timon et al, 2019 ). Some interventions have attempted the stimulation of the type II fibers by lifting heavy loads in strength tests within a percentage margin of load-intensity capable of ensuring 3-5 repetitions ( Blazevich and Babault, 2019 ; Kobal et al, 2019 ; Krzysztofik et al, 2020 ; Seitz and Haff, 2016 ). However, some CEs are stiff or do not provide the fluency and speed that the flywheel device is able to provide on the targeted joint kinetics ( Beato et al, 2019 ; MarotoIzquierdo et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Competitive athletes may offer highly different responses influenced by some intrinsic characteristics, such as the fiber-type distribution, muscular strength or training background ( Seitz and Haff, 2016 ; Wilson et al, 2013 ). In this regard, it has been reported that the PAPE phenomenon lacks optimal standards for both volume and intensity ( Kobal et al, 2019 ). For instance, speed-power athletes (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation